Perinatal factors associated with autistic spectrum disorder - Asri Yuniastuti; Tunjung Wibowo; Djauhar Ismail (Indonesian Pediatric Society, 2014)
Background The prevalence of autistic spectrum disorder(ASD) has increased in recent decades. The definitive causesof ASD have yet to be recognized. Howevei; it is believed thatboth genetic and non-genetic, as well as perinatal and post natalfactors influence ASD. Previous studies have shown inconsistentfindings.Objectives To assess for prematurity, birth weight, asphyxia,mode of delivery, bleeding during pregnancy, parental age andeducation, as prognostic factors for ASD.Methods We conducted a cross sectional study at schools forautistic children in Yogyakarta between February 2011 to October2012. The inclusion criteria were children with and without ASD,whose parents consented to participate in this study. Childrenwith genetic abnormalities or who planned to move away duringthe study period were excluded. A total of 48 subjects with ASDand 96 subjects without ASD were involved in this study. Datawere obtained by direct interview using questionnaires. Logisticregression analysis was performed to examine the hypoth esis.Results Multivariate analysis showed that prematurity was nota significant prognostic factor (RR 2.73; 95%CI 0.3 to 15.7) forASD. Howevei; children born by Caesarean section were 5.4 timesmore likely to have ASD (RR 5.4; 95%CI 1.3 to 22.8) comparedto those who were delivered vaginally or by vacuum extraction.Moreovet; asphyxia was also a significant prognostic factor forASD (RR 8.7; 95%CI 1.9 to 38.6) .Conclusion Prematurity is not a risk factor for ASD. Asphyxiaand Caesarean birth should be considered as potential confoundersin this study.